Present‐Day and Historical Aerosol and Ozone Characteristics in CNRM CMIP6 Simulations. (19th January 2020) - Michou, M.; Nabat, P.; Saint‐Martin, D.; Bock, J.; Decharme, B.; Mallet, M.; Roehrig, R.; Séférian, R.; Sénési, S.; Voldoire, A.
Abstract: Characteristics and radiative forcing of the aerosol and ozone fields of two configurations of the Centre National de Recherches Météoroglogiques (CNRM) and Cerfacs climate model are analyzed over the historical period (1850–2014), using several Coupled Model Intercomparison Project 6 (CMIP6) simulations. CNRM‐CM6‐1 is the atmosphere‐ocean general circulation model including prescribed aerosols and a linear stratospheric ozone scheme, while the Earth System Model CNRM‐ESM2‐1 has interactive tropospheric aerosols and chemistry of the midtroposphere aloft. The representations of aerosols and ozone in CNRM‐CM6‐1 are issued from simulations of CNRM‐ESM2‐1, and this ensures some comparability of both representations. In particular, present‐day anthropogenic aerosol optical depths are similar (0.018), and their spatial patterns correspond to those of reference data sets such as MACv2 and MACv2‐SP despite a negative bias. Effective radiative forcings (ERFs) have been estimated using 30‐year fixed sea surface temperature simulations (piClim) and several calls to the radiative scheme. Present‐day anthropogenic aerosol ERF, aerosol‐radiation ERF, and aerosol cloud ERF are fully within CMIP5 estimates and, respectively, equal to − 1.10, − 0.36, and − 0.81 W m − 2 for CNRM‐CM6‐1 and − 0.21, − 0.61, and − 0.74 W m − 2 for CNRM‐ESM2‐1. Additional CMIP6‐type piClim simulations show that these differences are mainly due to the interactivity of the aerosol scheme whose impact is confirmed when assessing the response of both climate model configurations to rising CO 2 . Present‐day stratospheric ozone ERF, equal to − 0.04 W m − 2, is in agreement with that of the CMIP6 ozone. No trend appears in the ozone ERF over the historical period although the evolution of the total column ozone is correctly simulated. Plain Language Summary: The manuscript documents the Météo‐France Centre National de Recherches Météorologiques aerosol‐chemistry modeling contributions to the sixth Coupled Model Intercomparison Project that supports the sixth IPCC Assessment Report of climate change. It establishes that their results are suitable for use by the scientific community in the analysis of the sixth Coupled Model Intercomparison Project experiments. The authors provide an evaluation of the model performance in both present‐day and historical (1850–2014) contexts, as well as a detailed analysis of the model calculated effective radiative forcing due to ozone and aerosols. Key Points: The representations of aerosol and ozone in the CMIP6 CNRM‐CM6‐1 and CNRM‐ESM2‐1 models is described Present‐day and historical aerosol and ozone distributions are assessed, as well as their effective radiative forcing (ERF) The present‐day anthropogenic aerosol ERF (‐1.10 W m − 2 for CNRM‐CM6‐1) is sensitive to the interactivity of aerosols